The Correlation between Students’ Watching English Animation Movie Habit with Their Vocabulary Mastery - Ni Kadek Sugi Juniari; Putu Ayu Paramita Dharmayanti; Anak Agung Putu Arsana (STKIP PGRI Tulungagung, 2021)
The study aims at figuring out the correlation between students’ watching English Animation Movie habit with the vocabulary mastery of the eleventh - grade students of SMAN 1 Sukawati in Academic Year 2020/2021. In the present study, the researcher specified the type of movie into animation movie which individual’s drawings, paintings, or illustrations are photographed frame by frame (stop-frame cinematography). The undertaking of the research was mainly based on the preliminary study. The subjects were the eleventh - grade students of SMAN 1 Sukawati in academic year 2020/2021. There were 60 subjects which came from 12 classes. The design was ex-post facto correlational research design. The research was carried out by distributing a questionnaire about students’ habit in watching English animation movies and a vocabulary test through google form. The result showed that there was significant correlation between students’ watching English Animation Movie habit with the vocabulary mastery of the eleventh - grade students of SMAN 1 Sukawati in Academic Year 2020/2021 with the correlation value was 0.719 that belonged to high correlation scale (0.600-0.800). In short, the study showed higher score that the students got in the questionnaire the higher score of vocabulary test that achieved.